Improving customer service and satisfaction of National Bank Limited (NBL): a study on Mirpur branch - Sadia, Safa (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.